Hypericin-bearing magnetic iron oxide nanoparticles for selective drug delivery in photodynamic therapy - Unterweger H (Dove Medical Press, 2015)
Harald Unterweger,1 Daniel Subatzus,1 Rainer Tietze,1 Christina Janko,1 Marina Poettler,1 Alfons Stiegelschmitt,2 Matthias Schuster,3 Caroline Maake,4 Aldo R Boccaccini,5 Christoph Alexiou11ENT Department, Section of Experimental Oncology and Nanomedicine (SEON), Else Kröner-Fresenius-Stiftung Professorship, University Hospital Erlangen; 2Institute of Glass and Ceramics, Department of Materials Science and Engineering, University Erlangen-Nuremberg, 3Materials for Electronics and Energy Technology, Department of Materials Science and Engineering, University Erlangen-Nürnberg, Erlangen, Germany; 4Institute of Anatomy, University of Zurich, Winterthurerstr, Zurich, Switzerland; 5Institute of Biomaterials, Department of Materials Science and Engineering, University Erlangen-Nuremberg, Erlangen, Germany Abstract: Combining the concept of magnetic drug targeting and photodynamic therapy is a promising approach for the treatment of cancer. A high selectivity as well as significant fewer side effects can be achieved by this method, since the therapeutic treatment only takes place in the area where accumulation of the particles by an external electromagnet and radiation by a laser system overlap. In this article, a novel hypericin-bearing drug delivery system has been developed by synthesis of superparamagnetic iron oxide nanoparticles (SPIONs) with a hypericin-linked functionalized dextran coating. For that, sterically stabilized dextran-coated SPIONs were produced by coprecipitation and crosslinking with epichlorohydrin to enhance stability. Carboxymethylation of the dextran shell provided a functionalized platform for linking hypericin via glutaraldehyde. Particle sizes obtained by dynamic light scattering were in a range of 55–85 nm, whereas investigation of single magnetite or maghemite particle diameter was performed by transmission electron microscopy and X-ray diffraction and resulted in approximately 4.5–5.0 nm. Surface chemistry of those particles was evaluated by Fourier transform infrared spectroscopy and ζ potential measurements, indicating successful functionalization and dispersal stabilization due to a mixture of steric and electrostatic repulsion. Flow cytometry revealed no toxicity of pure nanoparticles as well as hypericin without exposure to light on Jurkat T-cells, whereas the combination of hypericin, alone or loaded on particles, with light-induced cell death in a concentration and exposure time-dependent manner due to the generation of reactive oxygen species. In conclusion, the combination of SPIONs’ targeting abilities with hypericin’s phototoxic properties represents a promising approach for merging magnetic drug targeting with photodynamic therapy for the treatment of cancer. Keywords: magnetic drug targeting, photodynamic therapy, SPION, hypericin